Multicolour Fluorescence Based on Excitation‐Dependent Electron Transfer Processes in o‐Carborane Dyads. Issue 16 (24th January 2022) - Yang, Heyi; Liu, Haichao; Shen, Yunxia; Zhang, Shi‐tong; Zhang, Qing; Song, Qingbao; Lv, Chunyan; Zhang, Cheng; Yang, Bing; Ma, Yuguang; Zhang, Yujian
Abstract: Organic materials with excitation wavelength‐dependent (Ex‐de) emission are highly attractive for anticounterfeiting, optoelectronics and bioassay applications; however, the realization of Ex‐de fluorescence, independent of aggregation states, remains a challenge. We herein report a photoinduced electron transfer (PeT) strategy to design Ex‐de fluorescence materials by manipulating the relaxation pathways of multiple excited states. As expected, the o‐carborane dyad presents a clear Ex‐de fluorescence colour in the aggregated states, resulting from the tunable relative intensity of the dual‐fluorescence spectra. Taking TP[1]B as an example, the amorphous powders emitted bright blue‐violet, white and yellow colours under 390 nm, 365 nm and 254 nm UV illumination, respectively. Importantly, multicolour, flexible and transparent films as well as an anticounterfeiting application using this o ‐carborane dyad are demonstrated. Abstract : A universal photoinduced electron transfer (PeT) approach to construct dual‐fluorescence materials is presented. Impressively, the o ‐carborane dyads show multicolour fluorescence from single molecules due to the competition of nonradiative relaxation channels between internal conversion (IC) and PeT. Importantly, the multicolour, flexible and transparent films as well as an anticounterfeiting application using this dyad are well demonstrated.